2010
DOI: 10.1524/zkri.2010.1345
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental profile of MYTHEN detector in Debye-Scherrer geometry

Abstract: Instrumental line profile / Profile aberrations / Synchrotron radiation XRPD / Debye-Scherrer geometry / Position sensitive detector / MYTHEN / TOPAS / PM2K / WPPM Abstract. The main aberrations affecting data collected with 1D position sensitive detectors in Debye-Scherrer capillary geometry are examined, and analytical corrections proposed. The equations are implemented in two of the most advanced software based on the Rietveld and Whole Powder Pattern Modelling methods, respectively, for structure and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 27 publications
1
27
0
1
Order By: Relevance
“…Detailed information on how to use PM2K in combination with the MYTHEN detector can be found in Ref. [36]. Note that the diffraction patterns from the nc Ni and Ni-Fe samples exhibit very broad diffraction peaks.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed information on how to use PM2K in combination with the MYTHEN detector can be found in Ref. [36]. Note that the diffraction patterns from the nc Ni and Ni-Fe samples exhibit very broad diffraction peaks.…”
Section: Methodsmentioning
confidence: 99%
“…The intrinsic resolution of Mythen II in 2 is arctan(0.05/ 761.5) = 0.00376 . The effective resolution, however, is determined by the sample or illumination size, such that, for example, the resolution of data acquired from a homogeneously illuminated capillary of 200 mm diameter is 0.0188 (Gozzo et al, 2004(Gozzo et al, , 2010. In the large majority of cases, this is more than sufficient for PD applications, be they structural solutions, profile/full-pattern analysis or total scattering.…”
Section: Endstationsmentioning
confidence: 99%
“…They concluded that the peak intensity profile I(y), diffraction peak shift and peak profile shape variations were highly dependent on the displacement of the sample position from the true focusing point. Discussions on the nonlinear shift of the 2 positions due to capillary sample displacement away from the goniometer center when using position-sensitive detectors in Debye-Scherrer (transmission) geometry have been presented by Gozzo et al (2010) and Scarlett et al (2011). However, the maximum sample displacements investigated were less than 1 mm.…”
Section: Introductionmentioning
confidence: 99%